KELAYAKAN FINANSIAL PERIKANAN TANGKAP PURSE SEINE DI WILAYAH PESISIR BONTANG (Financial Feasibility Of Purse Seine Fisheries In Bontang Coastal Area) - IDHAMSYAH, IDHAMSYAH; ABDUSYSYAHID, SAID; SYAHRIR, MUHAMMAD; SUSILO, HERU; ABDUNNUR, ABDUNNUR; FITRIYANA, FITRIYANA (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2025)
Bontang City, whose territory faces directly to the Makassar Strait and is located in the fisheries management area (WPP 716), is an advantage. One of the potentials in the utilization of fisheries resources that is most dominant and contributes most to improving welfare for the community is fishing with Purse Seine gear. The purpose of this study is to assess the financial feasibility of fishing with Purse Seine gear in Bontang City. This research uses financial analysis method with Net Present Value investment criteria, Internal Rate of Return and Net B/C Ratio, Payback Period, and Return of Investment. The results obtained NPV value in the next thirteen years is Rp 2,317,683,710, IRR of 31%, NBCR 3.06, Payback Period for 3.5 years and ROI of 37.85%.